2021
DOI: 10.21512/lc.v15i1.7109
|View full text |Cite
|
Sign up to set email alerts
|

Language Politeness in the Javanese Verb Speech Level

Abstract: The focus of this research was the use of Javanese verb forms. The problem was studied with a sociolinguistic approach. The object of this research was the selection of Javanese verb forms used by speakers in the Magelang region. The informants were children, adolescents, and adults, both male and female. The informants in this research were 50 Javanese speakers. Data obtained by the technique of listening, recording, and taking notes. The problem was studied using speech component theory and language politene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 15 publications
0
1
0
1
Order By: Relevance
“…Poedjosoedarmo stated that the vocabulary at the Javanese speech level includes ngoko, madya, and krama. Ngoko is a form of speech that is disrespectful or informal; madya is semi-polite and semi-formal speech; and krama is a polite and formal form of speech (Atmawati, 2021). Besides vocabulary, politeness is also shown in how Javanese people address each other.…”
Section: Cultural Problemsmentioning
confidence: 99%
“…Poedjosoedarmo stated that the vocabulary at the Javanese speech level includes ngoko, madya, and krama. Ngoko is a form of speech that is disrespectful or informal; madya is semi-polite and semi-formal speech; and krama is a polite and formal form of speech (Atmawati, 2021). Besides vocabulary, politeness is also shown in how Javanese people address each other.…”
Section: Cultural Problemsmentioning
confidence: 99%
“…Studies on Javanese linguistic politeness are numerous. From a microlinguistic perspective, Krauße (2018) and Atmawati (2021) showed that politeness, honorific, and deferential systems are embedded in the Javanese vocabularies. Meanwhile, studies on politeness in various speech events reveal that by considering the context of situation, Javanese speakers actively adjust their words and expressions to convey politeness to show respect or intimacy, such as refusal strategies used by Javanese learners of English (Wijayanto, 2013), politeness strategies in Javanese political discourse (Santoso, 2015), strategies and levels of politeness in tourism-service language (Purnomo, 2016), and Javanese speech levels in transactional communication (Sumekto et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Volume: 8 Nomor : 4 Bulan : November Tahun : 2022 peneliti lain seperti penelitian tentang kesantunan bahasa Jawa (Wolff & Poedjosoedarmo, 2002;Atmawati, 2021) cenderung kepada bahasa yang digunakan secara umum tanpa klasifikasi umur dan strata sosial.…”
unclassified